Pulmonary arterial capacitance in patients with heart failure and reactive pulmonary hypertension. (11th November 2014) - Dragu, Robert; Rispler, Shmuel; Habib, Manhal; Sholy, Haitham; Hammerman, Haim; Galie, Nazzareno; Aronson, Doron
<x xml:space="preserve">Abstract</x> Aims Reactive pulmonary hypertension (PH) is a severe form of PH secondary to left‐sided heart failure (HF). Given the structural and functional abnormalities in the pulmonary vasculature that occur in reactive PH, we hypothesized that pulmonary artery capacitance (PAC) may be profoundly affected, with implications for clinical outcome. Methods and results We studied 393 HF patients of whom 124 (32%) were classified as having passive PH and 140 (36%) as having reactive PH, and 91 patients with pulmonary arterial hypertension (PAH). Mean PAC was highest in patients without PH (4.5 ± 2.1 mL/mmHg), followed by the passive PH group (2.8 ± 1.4 mL/mmHg) and was lowest in those with reactive PH (1.8 ± 0.7 mL/mmHg) (P = 0.0001). PAC and pulmonary vascular resistance (PVR) fitted well to a hyperbolic inverse relationship (PAC = 0.25/PVR, R2 = 0.70), with reactive PH patients dispersed almost predominantly on the flat part of the curve where a reduction in PVR is associated with a small improvement in PAC. Elevated PCWP was associated with a significant lowering of PAC for any PVR (P = 0.036). During a median follow‐up of 31 months, both reactive PH [hazard ratio (HR) 2.59, 95% confidence interval (CI) 1.14–4.46, P = 0.02] and reduced PAC (HR 0.72 per 1 mL/mmHg increase, 95% CI 0.59–0.88, P = 0.001) were independent predictors of mortality. Conclusions The development of reactive PH is associated with a marked reduction in PAC. PAC is a strong independent haemodynamic marker of mortality in HF and may contribute to the increased mortality associated with reactive PH.